Manajemen Pelayanan Pendaftaran Pasien Rawat Inap Bpjs Dalam Mengatasi Keterbatasan Tempat Tidur - Nurdiansyah, Reza; Sari, Irda (Jurnal Infokes, 2026)
This study aims to understand how BPJS inpatient service management deals with bed limitations at Hospital X. This study applies qualitative analysis and a descriptive approach. The methods used to collect data consist of direct observation in the field, interviews, and a review of literature relevant to the issue being discussed. The research found that there are factors that hinder the effectiveness of hospital services, namely the limited number of beds for inpatients, especially those covered by BPJS class III. The following suggestions are expected to overcome the existing problems: 1) provide temporary rooms, such as temporary care in BPJS class II rooms, and then transfer patients to class III rooms in accordance with their rights; 2) refer patients to other hospitals if BPJS class III beds and temporary care rooms are full. This study examines the management of BPJS inpatient services at Hospital X using qualitative methods. The results indicate that the limited number of Class III beds is the main constraint, with solutions including temporary rooms and referrals to other hospitals.